The Effect of Eight-Week Aerobic Training on Serum Angiotensin Converting Enzyme and Lipid Profile in Inactive Overweight Women - nahid Bijeh; Samaneh Farahati; Zahra Sarlak; Roghaieh Shad; Babak hooshmand moghadam (Fasa University of Medical Sciences, 2019)
Background & Objective: At present, the prevalence of hypertension is growing and one of the contributing factors in the occurrence and development of hypertension and atherosclerosis is impaired renin-angiotensin system which in this system endothelium angiotensin converting enzyme is the main enzyme. The aim of this study was to investigate the effect of eight weeks aerobic training on serum angiotensin converting enzyme and lipid profile in inactive overweight women. Materials & Methods: In this semi-experimental study, twenty healthy women (20-30 years old) with BMI>25 kg/m 2 were randomly divided into training group (n = 10) and control group (n = 10). The training group performed aerobic exercise for eight weeks, three sessions per week with 55-75% of maximum heart rate. The duration of each training session was increased from 40 to 60 minutes gradually. 48 hours before and after aerobic training program, anthropometric measurements, VO2max, lipid profile, angiotensin-converting enzyme (ACE) of all subjects were measured. Data were analyzed with paired t-independent test and t-student test at a significance level of P<0.05. Results: Results showed that eight weeks of aerobic training had a significant effect on weight (p=0/01) and BMI (p=0/01) in training group; While changes in angiotensin converting enzyme (p=0/543) and LDL(p=0/927), HDL(p=0/120), Triglyceride (p=0/788) and Cholesterol (p=0/324) during pre-test and post-test was not significant in between groups. Conclusion: Eight weeks of training program have improved angiotensin converting enzyme, LDL, HDL, Triglyceride and Cholesterol in women, approximately. And it can be said that regular exercise may probably have a preventive effect on the prohibition of cardiovascular disease in overweight women.